Epidemiology and Analysis of Mortality in Tertiary Care Hospital in a Metropolitan City, India: A Record Based Study - Vrushali Vishal Kulkarni; Amit Yadav (GAIMS Journal of Medical Sciences)
Background: Mortality statistics are essential for understanding population health, guiding public health efforts, and tracking disease trends. In India, reliable mortality data is often insufficiently documented and analyzed, limiting its utility for identifying leading causes of death.